A phase II study of TRC105 in patients with hepatocellular carcinoma who have progressed on sorafenib. Issue 5 (October 2015) - Duffy, AG; Ulahannan, SV; Cao, L; Rahma, OE; Makarova-Rusher, OV; Kleiner, DE; Fioravanti, S; Walker, M; Carey, S; Yu, Y; Venkatesan, AM; Turkbey, B; et al.
Background: Endoglin is an endothelial cell membrane receptor essential for angiogenesis and highly expressed on the vasculature of many tumor types, including hepatocellular carcinoma (HCC). TRC105 is a chimeric IgG1 anti-CD105 monoclonal antibody that inhibits angiogenesis and tumor growth by endothelial cell growth inhibition, ADCC and apoptosis, and complements VEGF inhibitors. Objective: The aim of this phase II study was to evaluate the efficacy of anti-endoglin therapy with TRC105 in patients with advanced HCC, post-sorafenib. Methods: Patients with HCC and compensated liver function (Childs-Pugh A/B7), ECOG 0/1, were enrolled to a single-arm, phase II study of TRC105 15 mg/kg IV every two weeks. Patients must have progressed on or been intolerant of prior sorafenib. A Simon optimal two-stage design was employed with a 50% four-month PFS target for progression to the second stage. Correlative biomarkers evaluated included DCE-MRI as well as plasma levels of angiogenic biomarkers and soluble CD105. Results: A total accrual of 27 patients was planned. However, because of lack of efficacy and in accordance with the Simon two-stage design, 11 patients were enrolled. There were no grade 3/4 treatment-related toxicities. Most frequent toxicities were headache (G2; N  = 3) and epistaxis (G1; N  = 4). One patient had a confirmed partial response by standard RECIST criteria and biologic response on DCE-MRI but the four-month PFS was insufficient to proceed to the second stage of the study. Conclusions: TRC105 was well tolerated in this HCC population following sorafenib. Although there was evidence of clinical activity, this did not meet prespecified criteria to proceed to the second stage. TRC105 development in HCC continues as combination therapy with sorafenib.